The Date and Content of P. Antinoopolis 12 (0232) - Kruger, Michael J. (New Testament studies, 2012)
P. Antinoopolis 12 (Aland 0232), a miniature codex containing remnants of 2 John, was considered by C. H. Roberts to be our earliest copy of this short epistle (third century) and also evidence of an early Johannine corpus. However, upon closer examination, both of these claims appear to be problematic. This article will argue that P.Ant. 12 is most likely a fifth-century codex (not third) and that it was far too small to have carried the entire Johannine corpus. Although there is no combination of books that fits perfectly into this codex, the most plausible suggestion seems to be that P.Ant. 12 originally held the book of Hebrews and the Catholic Epistles.